Labor market duality, regional growth, and poverty evolution - Pérez Méndez, Marco Antonio (Estudios Económicos de El Colegio de México, 2023)
This research shows some determinants of short term poverty evolution and differences of regional economic growth in Mexico. Links between informal duality as a differentiated break of regional economic growth and poverty driving related to the international crisis of 2008. We found regional economic dynamics is strongly related with informality of work and this duality allays economic growth and upgrades all increases on poverty in those regions strongly vinculated with global markets.